Capping Protein Regulator and Myosin 1 Linker 3 (CARMIL3) as a Molecular Signature of Ischemic Neurons in the DWI-T2 Mismatch Areas After Stroke - Yeh, Shin-Joe; Hsu, Pang-Hung; Yeh, Ti-Yen; Yang, Wei-Kang; Chang, Ko-Ping; Chiang, Chien-Sung; Tang, Sung-Chun; Tsai, Li-Kai; Jeng, Jiann-Shing; Hsieh, Sung-Tsang (Frontiers in Molecular Neuroscience, 2021)
Ischemic stroke with a mismatch between diffusion-weighted imaging (DWI) and fluid-attenuated inversion recovery (FLAIR) or T2-weighted images indicates onset within 4.5 h, but the pathological substrates in the DWI-T2 mismatch and T2(+) areas remain elusive. In this study, proteomics was used to explore (1) the protein expression profiles in the T2(+), mismatch, and contralateral areas, and (2) the protein with the highest expression in the T2(+) area in the brains of male Sprague-Dawley rats within 4.5 h after middle cerebral artery occlusion (MCAO). The expression of the candidate protein was further validated in (1) rat brain subjected to MCAO, (2) rat primary cortical neuronal culture with oxygen-glucose deprivation (OGD), and (3) infarcted human brain tissues. This study showed that apoptosis was observed in the T2(+) and mismatch regions and necroptosis in the T2(+) region of rat brains after MCAO. We identified capping protein regulator and myosin 1 linker 3 (CARMIL3) as the candidate molecule in the T2(+) and mismatch areas, exclusively in neurons, predominantly in the cytoplasm, and most abundant in the mismatch area. The CARMIL3(+) neurons and neurites in the mismatch and T2(+) areas were larger than those in the control area, and associated with (1) increased expression of sulfonylurea receptor 1 (SUR1), indicating edema, (2) accumulation of p62, indicating impaired autophagy, and (3) increase in 8-hydroxy-2'-deoxyguanosine (8-OHdG), indicating oxidative stress. The increased expression of CARMIL3 was validated in a cell model of cortical neurons after OGD and in infarcted human brain tissues. In conclusion, this study shows that the mismatch and T2(+) areas within 4.5 h after ischemia are characterized by upregulated expression of CARMIL3 in neurons, particularly the mismatch area, which is associated with neuronal edema, impaired autophagy, and oxidative stress, indicating that CARMIL3 serves as a molecular signature of brain ischemia.